HIV rapid diagnostic testing by lay providers in a key population-led health service programme in Thailand - Rapeeporn Wongkanya; Tippawan Pankam; Shauna Wolf; Supanit Pattanachaiwit; Jureeporn Jantarapakde; Supabhorn Pengnongyang; Prasopsuk Thapwong; Apichat Udomjirasirichot; Yutthana Churattanakraisri; Nanthika Prawepray; Apiluk Paksornsit; Thidadaow Sitthipau; et al. (Elsevier, 2018)
Introduction: Rapid diagnostic testing (RDT) for HIV has a quick turn-around time, which increases the proportion of people testing who receive their result. HIV RDT in Thailand has traditionally been performed only by medical technologists (MTs), which is a barrier to its being scaled up. We evaluated the performance of HIV RDT conducted by trained lay providers who were members of, or worked closely with, a group of men who have sex with men (MSM) and with transgender women (TG) communities, and compared it to tests conducted by MTs.Methods: Lay providers received a 3-day intensive training course on how to perform a finger-prick blood collection and an HIV RDT as part of the Key Population-led Health Services (KPLHS) programme among MSM and TG. All the samples were tested by lay providers using Alere Determine HIV 1/2. HIV-reactive samples were confirmed by DoubleCheckGold Ultra HIV 1&2 and SD Bioline HIV 1/2. All HIV-positive and 10% of HIV-negative samples were re-tested by MTs using Serodia HIV 1/2.Results: Of 1680 finger-prick blood samples collected and tested using HIV RDT by lay providers in six drop-in centres in Bangkok, Chiang Mai, Chonburi and Songkhla, 252 (15%) were HIV-positive. MTs re-tested these HIV-positive samples and 143 randomly selected HIV-negative samples with 100% concordant test results.Conclusion: Lay providers in Thailand can be trained and empowered to perform HIV RDT as they were found to achieve comparable results in sample testing with MTs. Based on the task-shifting concept, this rapid HIV testing performed by lay providers as part of the KPLHS programme has great potential to enhance HIV prevention and treatment programmes among key at-risk populations.